The Potential Role of Boron in the Modulation of Gut Microbiota Composition: An In Vivo Pilot Study - Nermin Basak Sentürk; Burcu Kasapoglu; Eray Sahin; Orhan Ozcan; Mehmet Ozansoy; Muzaffer Beyza Ozansoy; Pinar Siyah; Ugur Sezerman; Fikrettin Sahin (MDPI AG, 2024)
Background/Objectives: The role of the gut microbiome in the development and progression of many diseases has received increased attention in recent years. Boron, a trace mineral found in dietary sources, has attracted interest due to its unique electron depletion and coordination characteristics in chemistry, as well as its potential role in modulating the gut microbiota. This study investigates the effects of inorganic boron derivatives on the gut microbiota of mice. Methods: For three weeks, boric acid (BA), sodium pentaborate pentahydrate (NaB), and sodium perborate tetrahydrate (SPT) were dissolved (200 mg/kg each) in drinking water and administered to wild-type BALB/c mice. The composition of the gut microbiota was analyzed to determine the impact of these treatments. Results: The administration of BA significantly altered the composition of the gut microbiota, resulting in a rise in advantageous species such as Barnesiella and Alistipes. Additionally, there was a decrease in some taxa associated with inflammation and illness, such as Clostridium XIVb and Bilophila. Notable increases in genera like Treponema and Catellicoccus were observed, suggesting the potential of boron compounds to enrich microbial communities with unique metabolic functions. Conclusions: These findings indicate that boron compounds may have the potential to influence gut microbiota composition positively, offering potential prebiotic effects. Further research with additional analyses is necessary to fully understand the interaction between boron and microbiota and to explore the possibility of their use as prebiotic agents in clinical settings.